The Implementation Curriculum 2013 (K-13) in Teacher's Ability to Develop Learning Media at Distance Learning - Agus Hadi Utama (Universitas Veteran Bangun Nusantara, 2021)
After eight years of the launching Curriculum 2013 (K-13), it is expected that all schools and teachers have been able to implement the curriculum both in terms of preparation for learning media as well as in the learning process. However, the reality is far from expectations as the ability of teachers in the preparation of the learning media is still lacking. Detected through learning media compiled from teachers who are following the professional teacher education online, the results were far from expectations posing a big question mark for researchers. For this reason, the researchers tried to explore the issue through a qualitative descriptive approach. Although in this study quantitative data also exist, it was just as supportive data to strengthen the argument and conclusion. Sources of data in this study are a physical education, sports, and health teachers amounted 100 people. From these studies it was found that K-13 training has not met the need of all teachers reflected in learning media is not understood comprehensively by the teachers. Further, in some training, there are instructors who didn’t come from the field of physical education, sports, and health, but from other fields of study. This fact is of course very worrying as if it remains, the national education goal will never be reached. Therefore, it is necessary to reorder the instructors in accordance with expertise in the field of study as well as evaluating the effectiveness of the program.